2004
DOI: 10.1002/ijc.20410
|View full text |Cite
|
Sign up to set email alerts
|

Induction of a metastatogenic tumor cell type by neurotransmitters and its pharmacological inhibition by established drugs

Abstract: The active migration of tumor cells, a crucial requirement for metastasis development and cancer progression, is regulated by signal substances including neurotransmitters. We investigated the migration of tumor cells within a threedimensional collagen matrix using time-lapse videomicroscopy and computer-assisted analysis of the migration path. Tumor cell migration is induced by norepinephrine, dopamine and substance P. We show that this induced migration, using MDA-MB-468 breast and PC-3 prostate carcinoma ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
198
1
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 238 publications
(225 citation statements)
references
References 47 publications
18
198
1
2
Order By: Relevance
“…Polymorphisms of the βAR genes have been associated with diseases, including asthma (Chung et al 2011;Johnson 2001), obesity (Martinez et al 2003), and cancer (Wang et al 2006). In cancer, they are associated with cell proliferation and apoptosis (Meinhardt et al 1999;Sastry et al 2007), chemotaxis and metastasis (Entschladen et al 2002;Lang et al 2004;Shang et al 2009), and tumor growth (Shang et al 2009). Consistent with these results, βARs are also localized in epithelium, endothelium, nerve axons/processes, and mast cells (Chung et al 2011;Daly and McGrath 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphisms of the βAR genes have been associated with diseases, including asthma (Chung et al 2011;Johnson 2001), obesity (Martinez et al 2003), and cancer (Wang et al 2006). In cancer, they are associated with cell proliferation and apoptosis (Meinhardt et al 1999;Sastry et al 2007), chemotaxis and metastasis (Entschladen et al 2002;Lang et al 2004;Shang et al 2009), and tumor growth (Shang et al 2009). Consistent with these results, βARs are also localized in epithelium, endothelium, nerve axons/processes, and mast cells (Chung et al 2011;Daly and McGrath 2011).…”
Section: Discussionmentioning
confidence: 99%
“…1), rather than ionotropic receptors that directly gate ion channels in cellular membranes. 9 G proteins can affect various processes inside the cell, such as the level of cyclic AMP, and in doing so might influence carcinogenesis in complicated ways [60][61][62][63] that could have various time courses. A simple time course is that while a high level of NE is excessively stimulating its receptors on a cell, this increases the probability of immediately developing cancer within that cell; however, epidemiological drug studies suggest that there may be a significant delay, perhaps of many years.…”
Section: Literature Search Detailsmentioning
confidence: 99%
“…Indeed, data from many epidemiologic and experimental studies have revealed that the β-adrenergic receptor signaling pathway was involved in the proliferation, metastasis, and angiogenesis of several types of tumors [34][35][36]. Accumulating evidence has indicated that IH is a powerful sympathetic activator [37,38].…”
Section: Discussionmentioning
confidence: 99%